Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.18240/ijo.2023.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and associated factors of intraocular pressure in the older population: Tehran Geriatric Eye Study

Abstract: AIM: To determine the distribution and associated factors of intraocular pressure (IOP) in an Iranian elderly population 60 years of age and above. METHODS: The present report is part of the Tehran Geriatric Eye study (TGES), a population-based cross-sectional study that was conducted on the residents of Tehran 60 years of age and above. The sampling was performed using multistage stratified random cluster sampling methods from 22 districts of Tehran, Iran. Demographic and history information, blood samples, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The IOP is a variable with a linear trend and was previously analyzed in several other research studies. In a Tehran Geriatric Eye study report, the researchers found that an IOP ranging from 14 to 17 mm Hg was associated with older age and high systolic blood pressure [34]. A meta-analysis of European cohort studies reported an inverted U-shape trend, indicating that IOP increased until the age of 60 and then decreased again in older people [35].…”
Section: Discussionmentioning
confidence: 99%
“…The IOP is a variable with a linear trend and was previously analyzed in several other research studies. In a Tehran Geriatric Eye study report, the researchers found that an IOP ranging from 14 to 17 mm Hg was associated with older age and high systolic blood pressure [34]. A meta-analysis of European cohort studies reported an inverted U-shape trend, indicating that IOP increased until the age of 60 and then decreased again in older people [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies compared central corneal thickness between the diabetic and non-diabetic groups [ 18 ]. Although a number of studies found that diabetic patients had thicker corneas compared to non-diabetic subjects, [ 19 , 20 ] some other studies did not report any difference between the two groups [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%